REVIEW: Maintaining the climate struggle - Philip Cass (Asia Pacific Network, 2017)
An Inconvenient Sequel: Truth to Power, directed by Bonni Cohen, John Shenk. Produced by Richard Berge. Actual Films & Participant Media. Documentary. 2017. 98min.